ADCC: the rock band led by therapeutic antibodies, tumor and immune cells - Vincken, Roos; Armendáriz-Martínez, Uxue; Ruiz-Sáenz, Ana (Frontiers in Immunology, 2025)
Antibody-dependent cellular cytotoxicity (ADCC) is a critical mechanism by which therapeutic antibodies leverage the immune system to target and eliminate cancer cells. The key agents of ADCC are natural killer (NK) cells, specifically targeting antibody-covered cancer cells through the CD16 receptor. While other immune cells and Fc receptors can contribute and enhance ADCC, NK cells and the CD16 receptor are crucial for the efficacy of cancer therapies such as trastuzumab, cetuximab and rituximab. Co-culture assays are essential for understanding the mechanisms of these therapies, overcoming resistance and optimizing novel therapeutic antibodies. This review highlights the importance of measuring ADCC to assess the efficacy of therapeutic antibodies. Here we also present the various in vitro models and assay methodologies available for studying ADCC, comparing the strengths and limitations of approaches like using PBMCs to better reflect real-life conditions or NK cell lines for standardization. It also covers different readouts for ADCC, either focusing on effector cells activation, including reporter and degranulation assays or in the target cell killing, including different molecule release assays, flow cytometry and immunofluorescence techniques. Selecting the best model for studying ADCC is crucial for the translational significance of therapeutic antibody research.